2000
DOI: 10.1577/1548-8675(2000)020<0816:soislp>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Shrinkage of Inland Silverside Larvae Preserved in Ethanol and Formalin

Abstract: Length measurements of preserved larval fish are necessary in many types of larval fish surveys. If the fixative causes significant shrinkage, then the preserved lengths cannot be used to indicate accurate live lengths. The objective of this study was to determine how preservation in two different concentrations of formalin and ethanol affects the total length of larval inland silversides Menidia beryllina. Larvae were measured (nearest 0.1 mm) and individually fixed in one of four fixative treatments (80% eth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 9 publications
2
34
0
Order By: Relevance
“…Our results are consistent with those from other studies that indicated greater shrinkage in alcohol for larval fish (Fisher et al 1998, Cunningham et al 2000. Similarly, Distefano et al (1994) found preservative had no effect on the percentage of change in the overall length of central stoneroller (Campostoma anomalurn) after 90 and 180 day intervals.…”
Section: Small-bodied Stream Fishessupporting
confidence: 92%
See 1 more Smart Citation
“…Our results are consistent with those from other studies that indicated greater shrinkage in alcohol for larval fish (Fisher et al 1998, Cunningham et al 2000. Similarly, Distefano et al (1994) found preservative had no effect on the percentage of change in the overall length of central stoneroller (Campostoma anomalurn) after 90 and 180 day intervals.…”
Section: Small-bodied Stream Fishessupporting
confidence: 92%
“…Ethyl alcohol causes greater reduction in preserved larval fish length than forinalin (Kruse and Dalley 1990. Fisher et al 1998, Cunningham et al 2000, Moku et al 2004 were collected from the Kansas River, Riley County Kansas on 10 November 2005. The fish were visually sorted to obtain samples of similar total lengths (measured to the nearest millimeter), and then were placed into individually numbered sample bags containing 100 ml of one of the fixative solutions (5% and 10% formalin and 70% and 95% ethyl alcohol).…”
Section: Small-bodied Stream Fishesmentioning
confidence: 99%
“…To minimize the effect of shrinkage due to the fixation process, samples were analysed within 1 month after fixing (Fisher, Anderson & Willis 1998;Cunningham, Granberry & Pope 2000). Thereafter and until 45 dph, larvae were sample every 5 days.…”
Section: Methodsmentioning
confidence: 99%
“…Inaccurate measurements of body length and body weight are likely to cause errors in estimation of biological Morkert and Bergstedt 1990;Oozeki et al 1991;Fisher et al 1998;Smith and Walker 2003). However, the extent of shrinkage differs among fish species, developmental stages, and different kinds and/or concentrations of preservatives (e.g., Hay 1982; Leslie and Moore 1986;Kruse and Dalley 1990;Cunningham et al 2000;Moku et al 2004).…”
Section: Introductionmentioning
confidence: 99%